Supports materialization of Pd based catalysts for NOx removal by hydrogen assisted selective catalytic reduction in the presence of oxygen. Issue 20 (3rd September 2020) - Patel, Vivek Kumar; Sharma, Sweta
Abstract: The Pt and Pd based bimetallic catalyst are developed to address the NOx reduction activity. For this, a series of supports containing three different amounts of CeO2 −MgO (9 : 1, 3 : 1, and 3 : 2) are prepared by the co‐precipitation method, followed by impregnation of Pd metal precursors. The physicochemical properties of the catalytic system are investigated using various techniques such as Brunauer‐Emmett‐Teller (BET), X‐ray Diffraction (XRD), X‐ray photoelectron spectroscopy, Transmission Electron Microscopy (TEM), Raman spectroscopy, and H2 ‐TPR. Among all, Pd/CeO2 −MgO (3 : 1) gave the best NOx reduction activity. Furthermore, the effects of hydrogen concentration (0.2–0.8 vol %) on NOx reduction were tested. It was found that 0.8 vol % of H2 shows the highest NOx conversion. Subsequently, the successive impregnation of Pt metal over Pd based catalyst enhanced the catalytic properties. The bimetallic Pt−Pd/CeO2 −MgO (3 : 1) catalyst showed an 89 % NOx reduction with about 97 % N2 selectivity in broad temperature windows (100–300 °C). Abstract : The Catalyst Pd/CeO2 −MgO (3 : 1) prepared by precipitation followed by impregnation method shows the high NOx conversion and reasonable N2 selectivity with feed gas composition of 0.2 vol % H2, 1000 ppm NO, 6 vol % O2, rest Ar, and GHSV ∼20000 h −1 .